Multi-Media Occurrence of Antibiotics and Antibiotic Resistance Genes in East Dongting Lake - Guo, Xiaochun; Song, Ranran; Lu, Shaoyong; Liu, Xiaohui; Chen, Jinming; Wan, Zhengfen; Bi, Bin (Frontiers in Environmental Science, 2022)
With the extensive use of antibiotics, antibiotics and their induced resistance genes (ARGs) have become new types of pollutants widely distributed in a variety of environmental media. The contamination of antibiotics and ARGs occurring in important living and agricultural regions has aroused wide concern worldwide, especially in lake basins. The Dongting Lake basin is one of the important aquaculture and livestock areas in China, which is accompanied by a large amount of antibiotic use and discharge. However, the occurrence characteristics of antibiotics and ARGs in a multi-environment medium are still unclear. In this study, surface water and sediment samples in East Dongting Lake were collected by season, antibiotics and ARGs were quantitatively analyzed, and the risk quotient method was used to evaluate the ecological risk of antibiotics in surface water. 1) The concentration of antibiotics in the surface water of East Dongting Lake ranged from ND to 943.49 ng/L, with the maximum average concentration of 20.92 ng/L in spring. The concentration of antibiotics in sediments ranged from ND to 177.43 ng/g, with the maximum average concentration of 16.38 ng/g in fall. Ofloxacin (OFL) and sulfamethoxazole (SMX) were the main antibiotic pollutants in East Dongting Lake Basin. 2) sul1 and sul2 were the dominant ARGs in East Dongting Lake Basin. For spatial change, the total abundance of ARGs upstream was higher than that downstream. For seasonal change, the surface water and sediment were characterized by spring > summer > fall. 3) OFL and sulfamethoxazole might pose a significant high risk to aquatic organisms both in three seasons, and the ecological risk of antibiotics in East Dongting Lake is more significant at low temperatures than high. This study could provide important data information of the occurrence and concentration of antibiotics and ARGs in East Dongting Lake Basin.